Sistem Kepemimpinan Islami: Instrumen Inti Pengambil Keputusan pada Lembaga Pendidikan Islam - Afiful Ikhwan (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
Educational supervision, better known as education supervision, has a basic concept that is interconnected. Supervision that aims to improve the performance of educators and other school employees by providing good direction and guidance as well as input on good and professional methods or methods of education. The school administration business serves, assists and fulfills together to utilize resources, both personal and material, effectively and efficiently to support the achievement of the goal of education in schools optimally.